2014
DOI: 10.1007/s00455-014-9556-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supraglottic and Super-supraglottic swallows on Tongue Pressure Production against Hard Palate

Abstract: The objectives of this study were to evaluate the state of tongue pressure production during supraglottic swallow (SS) and super-supraglottic swallow (SSS) performed by healthy adults, and to investigate the effects of these swallowing maneuvers on the oral stage of swallowing. The participants were 19 healthy individuals. Tongue pressure against the hard palate during swallowing was measured using a tongue pressure sensor sheet system with five pressure-sensitive points. The tasks comprised swallowing 5 mL of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…This maneuver involves the patient holding a tight breath, swallowing while keeping the airway closed, then immediately coughing after the swallow. It has been shown in several studies that the super-supraglottic swallow has immediate effects on swallowing physiology [ 198 ]. Studies with relevant clinical endpoints are not available so far [ 164 ].…”
Section: Therapymentioning
confidence: 99%
“…This maneuver involves the patient holding a tight breath, swallowing while keeping the airway closed, then immediately coughing after the swallow. It has been shown in several studies that the super-supraglottic swallow has immediate effects on swallowing physiology [ 198 ]. Studies with relevant clinical endpoints are not available so far [ 164 ].…”
Section: Therapymentioning
confidence: 99%
“…Ultimately, the remedial approach works to improve swallowing function through various exercise and manoeuvres (e.g. head lift, Mendelsohn manoeuvre and supraglottic swallowing) . Conversely, the compensatory approach promotes safer swallowing with control of food intake, material, viscosity and the use of specific postures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A study previously had shown that supraglottic swallow applied in an intervention group could significantly improve the breathing-swallowing coordination, so that it protected the respiratory track better. 18 Effectiveness of swallowing therapy is also affected by the structure of the semisolid food used in the intervention. A previous study revealed a decrease of pharyngeal residue in patients with post-stroke dysphagia who consumed semisolid food.…”
Section: Discussionmentioning
confidence: 99%